Methods of Talmud Study and Teaching at the Central Schools of Learning in 19th Century Eastern Europe and Germany (Arquivo Maaravi: Revista Digital de Estudos Judaicos da UFMG, 2019)
This article deals with the various methods of teaching the Babylonian Talmud, utilized at the central schools of Jewish learning in Eastern Europe and Germany about one hundred and fifty years ago. We shall present the various methods of teaching characteristic of these schools of learning and ways of teaching Talmud, features of the methods, from that period to the modern method in the first academic institutions in Berlin. The modern teaching method took the innovative form of academic research, which was taking its initial steps but in practice laid the foundations for academic research conducted to this day.